Unanimity under Ambiguity - Simona Fabrizi; Steffen Lippert; Addison Pan; Matthew Joseph Ryan (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2021)
Ellis (2016) introduced a variant of the classic (jury) voting game in which voters have ambiguous prior beliefs. He focussed on voting under majority rule and the implications of ambiguity for Condorcet's Theorem. Ryan (2021) studied Ellis's game when voting takes place under the unanimity rule. His focus was on the implications of ambiguity for the "jury paradox" (Feddersen and Pesendorfer, 1998). Neither paper described all equilibria of these games, though both authors identified equilibria with a very different structure to those in the respective games without ambiguity. We complete the description of all equilibria of voting games under the unanimity rule. In particular, we identify equilibria having the same form as those in Feddersen and Pesendorfer (1998), as well as equilibria with a "dual" form.
Keywords: 330